Chapter Memorie autobiografiche come patrimonio di comunità - Benelli, Caterina (Studi e saggi, 2019)
We live in a historical period in which it is necessary and urgent to know and relate to stories. Today, the social function of memory is stronger and more evident than ever. The concept of memory, as well as that of recollection, is widely used, but those who resort to it are not always able to fully grasp its meaning. As a matter of fact, the educational function of memory is also expressed through narration. There is no narration and writing of oneself that does not bring within the testimony of a historical time, of a social group and of a precise epoch that reveals unusual nuances and situations, eager to be discovered and to become part of the social heritage. The oral and written narration allows narrators to feel part of a community, to feel in a "warm" place, in a comfortable area and part of a community rich in mutual interest and able to guarantee the rights of all and a reciprocal recognition. Addressing the question of the memory of a community in an era of fragility, of borders, of spaces shared more and more virtually and less physically, means to contrast isolation and the relational distance between people. Life stories provide us with descriptions and observations of how we live in a place, in a territory, in a family, in a school, in a company, in any situation in which human beings have exchanged stories and have learned from each other. The intent to collect the memories of the community, through life stories, autobiographies, arises from the need to look at the traces left by those who preceded us to better understand and face the future, that is, to pay attention to micro-stories. This contribution aims at reflecting on the educational and social value of autobiographies as important instruments for observation, investigation, analysis and restitution of new insights on the community through the educator's role as a facilitator with autobiographical skills.